2023
DOI: 10.3390/jpm13020311
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Transforaminal Lumbar Interbody Fusion in the Ambulatory Surgery Center and Traditional Hospital Settings, Part 1: Multi-Center Assessment of Surgical Safety

Abstract: (1) Background: The technological advances achieved with minimally-invasive surgery have enabled procedures to be undertaken in outpatient settings, and there has been growing acceptance of performing minimally-invasive transforaminal interbody fusion (TLIF) in the ambulatory surgery center (ASC). The purposeof this study was to determine the comparative 30 day safety profile for patients treated with TLIF in the ASC versus the hospital setting. (2) Methods: This multi-center study retrospectively collected ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Eight studies with a total of 42,995 IPS patients and 3,593 OPS patients were included for readmission 18,20–22,25,27–29 . The Pooled readmission rate was 3.4% (0.7%–8.2%) in the OPS cohorts and 4.2% (1.6%–8%) in the IPS cohorts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies with a total of 42,995 IPS patients and 3,593 OPS patients were included for readmission 18,20–22,25,27–29 . The Pooled readmission rate was 3.4% (0.7%–8.2%) in the OPS cohorts and 4.2% (1.6%–8%) in the IPS cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…4). Twelve studies with a total of 70,106 IPS patients and 5135 OPS patients were included for surgical complications 18,20–26,28–31 . The meta-analysis of 12 studies showed significantly decreased odds of surgical complication rates among OPS compared with IPS [OR=0.41 (0.50–0.68), P =<0.001, I2=37.9%] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5 Comparative studies evaluated differences in perioperative baseline characteristics, operative efficiency, and 30-day safety events for patients undergoing MIS-TLIF in a hospital vs an ASC and highlighted similar safety profiles and clinical outcomes in ASC compared with traditional hospital settings. [6][7][8][9] There is also a growing acceptance of performing MIS-TLIF in ASCs, indicating a shift in surgical practices toward more cost-effective and patient-friendly environments. This trend is partly facilitated by certain technological advancements, such as navigation and robotics, which facilitate MIS-TLIF in outpatient settings.…”
Section: Introductionmentioning
confidence: 99%